2014
DOI: 10.3945/jn.113.178616
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection, Viral Load, Low Birth Weight, and Nevirapine Are Independent Influences on Growth Velocity in HIV-Exposed South African Infants

Abstract: Data from a prospective multisite cohort study were used to examine the effect of HIV exposure, untreated HIV infection, and single-dose nevirapine on infant growth velocity. The 2009 WHO growth velocity standards constitute a new tool for this type of investigation and are in need of functional validation. In period 1 (3-24 wk), 65 HIV-infected, 502 HIV-exposed uninfected (HEU), and 216 HIV-unexposed infants were included. In period 2 (25-36 wk), 31 infants moved from the HEU group to the HIV-infected group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 25 publications
4
35
1
Order By: Relevance
“…While inferior growth patterns have been reported in several studies, these studies differ from our design in that all not HIV-EU participated in PMTCT care until the time of growth measurement [16,32,33] and/or that weaning was considerably earlier in HIV-EU [32,33]. In agreement with our findings, other studies with continued PMTCT-like follow-up [34,35] and similar feeding practice [34] found non-inferior growth in HIV-EU infants.…”
Section: Discussionsupporting
confidence: 82%
“…While inferior growth patterns have been reported in several studies, these studies differ from our design in that all not HIV-EU participated in PMTCT care until the time of growth measurement [16,32,33] and/or that weaning was considerably earlier in HIV-EU [32,33]. In agreement with our findings, other studies with continued PMTCT-like follow-up [34,35] and similar feeding practice [34] found non-inferior growth in HIV-EU infants.…”
Section: Discussionsupporting
confidence: 82%
“…Thirty‐seven reports, from 29 studies conducted in 12 African countries and involving 32 173 (11 164 HEU) children, were included, as shown in Figure (characteristics of and reasons for the exclusion of studies are shown in Appendix S5; characteristics of included studies are shown in Appendix S6). Three studies contributed data on the same outcome at different time points (mortality , neurodevelopment and growth , respectively); while five studies contributed two reports each, on different outcomes . Overall, 28 prospective studies were included , of which 11 were randomised controlled trials (13 reports), and two interventional cohort studies (four reports) focusing on PMTCT .…”
Section: Resultsmentioning
confidence: 99%
“…Since 2015, WHO recommends universal ART for all HIV‐infected individuals, irrespective of disease stage, and in line with this, ‘Option B+’ as the preferred PMTCT strategy . Effective use of maternal ART results in viral suppression with subsequent immune restoration and protection of maternal health ; HEU infants born to mothers with lower HIV viral load and/or higher CD4 count are at significantly lower risks of death , hospitalisation , severe infection , immune dysfunction and growth faltering than those born to women with untreated or advanced HIV disease .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we did not have information on the HIV status of the infant at birth which has been shown to be associated with SGA and preterm delivery. 28, 29 However, both maternal HIV severity and fetal HIV acquisition might be intermediates on the pathway between ARV exposure and SGA, in which case adjusting for them in the analyses would require advanced methods and more granular information of the intermediates. 30 Also, greater than 30% pregnancies had missing information on illicit drug and alcohol use, both of which are major risk factors for SGA and may be important confounders of the association between exposure to ARVs and SGA.…”
Section: Discussionmentioning
confidence: 99%